Dynamic Holocene Vegetation and North Pacific Hydroclimate Recorded in a Mountain Peatland, Moloka‘i, Hawai‘i - Beilman, David W.; Massa, Charly; Nichols, Jonathan E.; Elison Timm, Oliver; Kallstrom, Russel; Dunbar-Co, Stephanie (Frontiers in Earth Science, 2019)
The Hawaiian Islands are the only high land in a vast stretch of the North Pacific where past climatological and ecological processes can be reconstructed from terrestrial Earth system archives. We measured hydroclimatic proxies and carbon accumulation in an organic sediment core from the windward montane peatland Pēpē‘ōpae on the Island of Moloka‘i, Hawai‘i using radiocarbon, leaf wax geochemistry, and stable isotopes of carbon and hydrogen in addition to historical pollen records. Following a period of soil development, substantial carbon accumulation began around 10 ka BP (thousands of years before present) under wet conditions. Peat formation was continuous but variable throughout the Holocene, including maxima in carbon accumulation around 9 and 3 ka and a minimum around 1.5 ka that has resulted in a belowground carbon storage today of 144 kg C m-2. From this core we generated a new chronology for previously published pollen spectra from the study site and a Wetness Index that shows increases in dry-adapted taxa in upwind forests during periods of decreased carbon accumulation in the peatland. Shifts in the distribution of sedimentary n-alkane chain lengths in the context of 14 species of modern bog plant n-alkanes suggests litter inputs have been derived from a diverse plant community that changed in dominant species in response to climate. Hydrogen stable isotope ratios of sedimentary C29n-alkanes show negative departures around 9 and 3 ka consistent with increases in storm-derived rainfall likely related to the position and strength of the northern jet stream. This study is the first to provide a continuous organic sedimentary record of links between hydroclimate, vegetation, and montane belowground carbon sequestration for this part of the North Pacific.